Detection of a Pack-Photon: A Theoretical Analysis (Global Journal of Science Frontier Research, 2020)
The Observational prove which will result in the final acceptance of the Theory of Everything is the detection/discovery of a pack photon. In this paper, an analysis on the nature and existence of a pack-photon is described, this includes major characteristics and properties. A clue which will help certain organizations with telescopes/photon detectors at the outer space to detect a pack photon is also explained in this paper.
Keywords: electromagnetic radiation; pack photon; wavelength